Lipase-catalyzed acylation of levoglucosan in continuous flow: antibacterial and biosurfactant studies. Issue 5 (21st January 2022) - do Nascimento, Marcelo A.; Vargas, Juan P. C.; Rodrigues, José G. A.; Leão, Raquel A. C.; de Moura, Patricia H. B.; Leal, Ivana C. R.; Bassut, Jonathan; de Souza, Rodrigo O. M. A.; Wojcieszak, Robert; Itabaiana, Ivaldo
Abstract : Ipase-catalyzed transesterification of LG under continuous flow conditions. Abstract : Studies involving the transformation of lignocellulosic biomass into high value-added chemical products have been intensively conducted in recent years. Its matrix is mainly composed of cellulose, hemicellulose and lignin, being, therefore, an abundant and renewable source for obtaining several platform molecules, with levoglucosan (LG) standing out. This anhydrous carbohydrate can be acylated to obtain carbohydrate fatty acid esters (CFAEs). Here, these compounds were obtained via enzymatic acylation of LG, commercially obtained (Start BioScience®), with different acyl donors in continuous flow. Through the experimental design using a model reaction, it was possible to optimize the reaction conditions, temperature and residence time, obtaining a maximum conversion at 61 °C and 77 min. In addition, there was a productivity gain of up to 100 times in all comparisons made with the batch system. Finally, CFAEs were applied in tests of interfacial tension and biological activity. For a mixture of 4- and 2- O -lauryl-1, 6-anhydroglucopyranose (MONLAU), the minimum interfacial tension (IFT min ) obtained was 96 mN m −1 and the critical micelle concentration (CMC) was 50 mM. Similar values were obtained for a mixture of 4- and 2- O -palmitoyl-1, 6-anhydroglucopyranose (MONPAL), not yet reported in the literature, of 88 mN m −1 in 50 mM. For a mixture of 4- and 2- O -estearyl-1, 6-anhydroglucopyranose (MONEST) and 4- and 2- O -oleoyl-1, 6-anhydroglucopyranose (MONOLE), CMC was higher than 60 mM and IFT min of 141 mN m −1 and 102 mN m −1, respectively. Promising data were obtained for minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of MONLAU against Staphylococcus aureus strains at 0.25 mM.